Implementation of the Composite Performance Index and Rank Order Centroid Weighting Methods in E-Wallet Selection - Susana Dwi Yulianti; Rini Nuraini; Arisantoso Arisantoso; Mursalim Tonggiroh (Institut Teknologi dan Bisnis Bina Sarana Global, 2023)
Nowadays, e-wallets have become a popular alternative for non-cash financial transactions. More and more e-wallet companies and service providers are emerging with various features and benefits. To determine the choice of using an e-wallet, users must know each e-wallet's various features and services; of course, this takes time and makes it difficult for decision-makers. This research aims to implement the Composite Performance Index (CPI) and Rank Order Centroid (ROC) approaches in a decision support system for choosing an e-wallet to produce easy and fast decisions. The ROC method is used to determine the weight value based on the order of importance of the criteria. Meanwhile, the CPI approach has the ability to combine information from various criteria into one index and evaluate differences in criteria to obtain alternative rankings. This research produces a website-based DSS application that recommends the best alternative by displaying alternative rankings. The system built produces valid calculation output; this is proven by the results of calculations by the system and manual calculations showing the same results. For software testing with usability testing, an average value of 86% was obtained. This means that the software developed is feasible to implement and considered easy to use.